Mexico under misplaced monopolies concentrated wealth and growing violence from the 1980s to the present - González González, Francisco Enrique 1970- (Europa emerging economies, 2018)
This is a highly original investigation that will interest people who follow Mexican politics and its economy. The analytical framework will be of use to analysts, scholars, and students of comparative political economy, democratization studies, market reforms, and security and conflict studies